Tinjauan Yuridis Sosiologis Tentang Perjanjian Pinjaman Tanpa Jaminan Di Unit Pengelola Kegiatan (UPK) Di Suela, Lombok Timur - Baiq Annisya Desti Aulia; M. Yazid Fathoni (Fakultas Hukum Universitas Mataram, 2022)
The aims of this study is to identify and analyze unsecured loan agreements, especially in the Activity Management Unit (UPK). This study uses an empirical normative research method with conceptual approach, statute approach, and sociological approach. The agreement without any guarantee is one of the Community Empowerment Trust Fund (DAPM) programs in poverty reduction efforts. Based on the results of the research, the problems that arise are default in the form of bad loans and transfer of loan payments that occur due to several factors. The solution is to carry out several stages without giving a fine to the debtor.